Subwavelength pixelated CMOS color sensors based on anti-Hermitian metasurface - Joseph S. T. Smalley (Nature Portfolio, 2020)
Pixel size in imaging and displays is limited by fundamental constraints that compromise performance at wavelength scales. Here the authors present subwavelength color pixel sensors based on anti-Hermitian metasurfaces relying on structural color for increased performance.